2020
DOI: 10.1371/journal.pone.0238005
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metabolic syndrome in patients with lichen planus: A systematic review and meta-analysis

Abstract: Background Studies have investigated whether patients with lichen planus are at a high risk of metabolic syndrome; however, currently, no conclusive data are available in this regard. Objective This meta-analysis was performed to analyze the published literature investigating the association between metabolic syndrome and lichen planus. Method Two reviewers independently searched 4 databases (PubMed, Embase, the Cochrane Library and Web of Science) for observational studies assessing the prevalence of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
(45 reference statements)
0
17
0
3
Order By: Relevance
“…El caso reportado presenta características clínicas e histológicas coincidentes con la literatura, con la diferencia que se trata de un hombre y el LPO se ha reportado con predominio en mujeres (3). Así mismo, se trata de un paciente diabético e hipertenso con niveles elevados de LDL, lo que resulta importante, ya que los pacientes con LP tienen más probabilidades de desarrollar síndrome metabólico (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El caso reportado presenta características clínicas e histológicas coincidentes con la literatura, con la diferencia que se trata de un hombre y el LPO se ha reportado con predominio en mujeres (3). Así mismo, se trata de un paciente diabético e hipertenso con niveles elevados de LDL, lo que resulta importante, ya que los pacientes con LP tienen más probabilidades de desarrollar síndrome metabólico (12).…”
Section: Discussionunclassified
“…Estos síntomas clínicos pueden hacer que los pacientes sean propensos al desarrollo de estrés, ansiedad y depresión, lo que empeora el cuadro (11). Además, el LP se ha relacionado con numerosas connotaciones sistémicas como diabetes mellitus (DM), hipertensión, síndrome metabólico, enfermedades de la tiroides, dolencias psicosomáticas, enfermedad hepática crónica, enfermedades gastrointestinales y susceptibilidad genética al cáncer (4,12,13).…”
Section: Introductionunclassified
“…Li et al (2020) observed that is not associated with CVD [49]; however, Cheng et al (2020) found that rosacea is associated with hypertension and high levels of LDL and low HDL [50]. Furthermore, people presenting lichen planus (LP), which is an idiopathic inflammatory dermatosis, are more likely to be affected by MetSyn [51].…”
Section: Indicators Related To Associated Diseases/syndromesmentioning
confidence: 99%
“…One of other types is eruptive LP, which presents with numerous papules spread on the large body surface. Nowadays, LP is suspected to be associated with MS, similar to psoriasis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their pathogenesis is not fully understood, but autoimmune factors are suspected as one of the possible paths, along with drugs, infections, and stress that can trigger the lesions’ occurrence [ 12 , 15 ]. Moreover, both PSO and LP have been related to components of MS [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%